2012
DOI: 10.1111/j.1471-0528.2011.03218.x
|View full text |Cite
|
Sign up to set email alerts
|

Is first‐trimester crown–rump length associated with birthweight?

Abstract: We wish to thank Dr Tiran Dias and Professor Basky Thilaganathan 1 for their comments on our recent publication about the association between crown-rump length (CRL) and birthweight. 2 They comment on our method to date pregnancies following in vitro fertilisation (IVF). Indeed, gestational age (GA) was calculated by adding 14 days to the number of days between the date of oocyte retrieval and the date of ultrasound examination. This seems an appropriate method because fertilisation was performed on the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
1
14
0
2
Order By: Relevance
“…The accurate estimation of fetal weight, size, growth rate, and gestational age can lead to the diagnosis of several perinatal conditions, and therefore have an important role in reducing perinatal morbidity and mortality [3]. Since growth patterns in the first trimester are among the chief factors determining birth weight, a fetus small for gestational age in the first trimester will still be small for gestational age at delivery [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The accurate estimation of fetal weight, size, growth rate, and gestational age can lead to the diagnosis of several perinatal conditions, and therefore have an important role in reducing perinatal morbidity and mortality [3]. Since growth patterns in the first trimester are among the chief factors determining birth weight, a fetus small for gestational age in the first trimester will still be small for gestational age at delivery [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al has shown that a first‐trimester crown–rump length (CRL) that is 2 to 6 days smaller than expected is associated with an increased risk for low birthweight (LBW) and SGA. This association was also seen both prospectively and retrospectively in women who conceived as a result of assisted reproductive technology (ART) . Most recently Mook‐Kanamori et al confirmed an increase risk of LBW and delivery of an SGA infant in the setting of first trimester fetal growth restriction.…”
Section: Introductionmentioning
confidence: 92%
“…For example, Graca et al 28 examined cerebral volumes during the first postnatal week in 128 infants and found that brain volumes are highly correlated with birth weight. Furthermore, fetal growth as documented by ultrasound during the first 29 and second 30 trimesters has been shown to influence postnatal birth weight. Given the important association between prenatal brain development and postnatal birth weight, our findings of modest birth weight reduction in CWE may provide the earliest indicator for the origin of abnormal neurodevelopment.…”
Section: Birth Weight In Children With Epilepsymentioning
confidence: 99%